Using the fuzzy linguistic computing in the evaluation of the value creation in an innovative product - Pedro, M. I.; Sarmento, M.; Silva, M.; Filipe, J. (MCDM methods for business and management, 2020)
Although innovation usually involves the assumption of high risk levels, it assumes itself as a vital tool for growth, enhancing value creation representing a competitive advantage. The aim of this chapter is to propose a methodology to evaluate the potential for value creation in innovation of a new product, relatively to intangible and tangible assets. For intangible assets the proposed methodology combines a multiple criteria decision-making method with an adaptation of Tai and Chen (2009) model using 2-tuple fuzzy linguistic approach. This methodology was applied to the EToll product developed by the Portuguese company Brisa Innovation and Technology. It was concluded that the benefits that most contributed to value creation are the development and entrepreneurship of national companies and a better cooperation with suppliers and partners. The EToll also allowed a significant reduction in operating costs in the company. The originality of this study is based in the challenge for business managers to assess the real impact of new products based not only on financial reports, but also in terms of intangible assets and also, how to consider the more appropriate qualitative dimensions to evaluate the performance of intangible assets resulting from innovation.